Investigation of Thermal and Antimicrobial Properties of NiTiX (X = Ta, Ag, and Nb) Shape Memory Alloys - Aydogdu, Yildirim; Abboosh, Omar; Soyer, Pervin; Kilic, Gokhan; Savur, Asena; Dagdelen, Fethi; Tunali, Yagmur (Maik Nauka/Interperiodica/Springer, 2022)
In this study, the Ni30Ti50Ta20, Ni30Ti50Ag20 and Ni29Ti50Nb21 shape memory alloys SMAs were produced through the arc-melting method under a high vacuum. The thermal properties and antimicrobial potential for these alloys were investigated. The thermal properties were determined by DSC at different heating rates. According to the DSC results, the austenite phase transformation temperature of Ni30Ti50Ta20 alloy is higher than Ni30Ti50Ag20 and Ni29Ti50Nb21 alloys. The thermal activation energy calculated by Kissinger and Ozawa methods were found as follows: E-a = 156.138 kJ/mol and E-a = 154.37 kJ/mol for Ni30Ti50Ta20 alloy, E-a = 124 kJ/mol and E-a = 123.74 kJ/mol for Ni30Ti50Ag20 alloy, and E-a = 89.43 kJ/mol and E-a = 90.6 kJ/mol for Ni29Ti50Nb21 alloy, respectively. In this study each of alloys exhibited a very strong antifungal ability. When compared by the antibacterial activities; the Ni30Ti50Ta20 alloy was showed higher activity than Ni30Ti50Ag20 and Ni29Ti50Nb21 alloys. It was seen from the Vickers hardness results of the samples that Ni30Ti50Ta20 SMA has the highest value. Optical microscope images of the alloys were taken at three different temperatures. Martesite plates were not found in any of the alloys. In addition, no structural changes were observed with the temperature difference. Based on the obtained results, it is suggested that the alloys have a high potential for biomedical applications to prevent bacterial based infections.
Keywords: biomedical; antifungal; NiTi; shape memory alloy; activation energy